Chef Roy Choi and the street food remix - Martin, Jacqueline Briggs; Lee, June Jo (Readers to Eaters Books, 2017)
Describes the popular street cook's life, including working in his family's restaurant as a child, figuring out what he wanted to do with his life, and his success with his food truck and restaurant.